Co-digestion of the organic fraction of municipal solid waste with primary sludge at a municipal wastewater treatment plant in Turkey - Dereli, Recep Kaan; Ersahin, Mustafa Evren; Gomec, Cigdem Yangin; Ozturk, Izzet; Ozdemir, Ozgur (SAGE Publications, 2009)
Co-digestion of the organic fraction of municipal solid waste (OFMSW) and sewage sludge may be an attractive alternative for sustainable management of two separate waste streams produced in large amounts in all countries. This study evaluates calculation-based results of an anaerobic co-digestion process for primary sludge (PS) together with the OFMSW. The calculations were carried out for the anaerobic digester of Kayseri municipal wastewater treatment plant (in Turkey) presently digesting only PS. Two alternatives were proposed using different solid waste contents in co-digesters. For achieving the optimal solids content, some treated wastewater should be recycled to the inlet of the digesters. The municipal solid waste collection method characterized as mechanically sorted (MS-OFMSW; Option 1) is evaluated as well as a source sorted (SS-OFMSW) alternative (Option 2). Utilizing the energy produced by the existing sludge digester, only 30% of the internal energy demand at the wastewater treatment plant can be covered. The aim of this study is to evaluate how energy production would be increased by co-digestion of OFMSW and PS. The best operational condition considering organic loading rate, hydraulic retention time and energy generation could be attained at 10% digester solids content for both options. According to Option 1, almost 77% of the energy demand could be covered by co-digestion of MS-OFMSW and PS. Results indicated that almost 100% energy coverage can be obtained when co-digestion (Option 2) was performed according to SS-OFMSW and PS.
Keywords: Waste Products; Sewage; Turkey; Waste Disposal, Fluid; Refuse Disposal; Biodegradation, Environmental; Bioreactors; Metals, Heavy; Anaerobiosis; Cities